Comprehensive assessment of factors that have a significant impact on the technical condition of draglines - Kritsky D.Y.; Fedorov A.V.; Andreeva L.I. (Горное оборудование и электромеханика)
The article presents the main results of the research carried out by the authors, analyzes the factors that significantly affect the technical condition of walking dragline excavators. It has been established that the more significant factors limiting the use of high-performance draglines are: the current technical condition of the excavator (premature wear and high deformation of load-bearing structures: support base, rotary platform; unacceptable wear of gear elements, degradation of electrical equipment); the professionalism of excavator management (weak repair discipline of the implementation of the schedule of maintenance work, the age qualification of personnel, professionalism and skills of excavator management); the quality of spare parts and materials (lack of supply of high-quality spare parts for foreign-made machinery, poor quality of spare parts manufacturing at domestic enterprises, long production and delivery times to the Customer's enterprise). It was also noted that long downtime in the repair of large-scale mining equipment related to climatic conditions and the lack of necessary components affect the technical and economic performance of the enterprise and hinder the development of mining operations. It should be noted that, compared with other types of machine-building products, walking excavators with significant dimensions and weights have a number of features as repair facilities: the need for powerful lifting mechanisms; equipment for storage of components and assemblies of a walking excavator; the need to equip special repair sites; a large amount of dismantling and installation repairs, etc. Obviously, due to the extreme importance of the problem of reliability of mining machinery and equipment for transportless stripping, research needs to be significantly intensified and excavator manufacturers, production associations and the scientific community must be involved in this research.